Ergonomics intervention for assembly table in aircraft manufacturing company - Nur Ainaa Razali@Ngah (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this to solve problrm issur at aircraft manufacturing company. The study adopted some of assessment tools to define the problem occurs at the Aeropace Composite Malasia. The problem was identified that need some improvement of activities by workers that effect lo back pain problem by developing new tool to make sure the activities will be more ergonomics The objective of this project are to identify argonomics issue in assembly table, to assess current risk on worker when working at assembly and to design a suitable ergonomics tool or equipment to improve assembly table RULA and ART assessment were applied tool assess the risk as the measurement tool for ergonomics practice applied.It had shown that the score risk before improvement is high,where the score risk after intervention is decrease.Based on human model analysis in CATIA,it shown that the intervention had improved the task and worker's posture